Minimal Access (Endoscopic and Robotic) Breast Surgery in the Surgical Treatment of Early Breast Cancer—Trend and Clinical Outcome From a Single-Surgeon Experience Over 10 Years - Lai, Hung-Wen; Chen, Shou-Tung; Lin, Ying-Jen; Lin, Shih-Lung; Lin, Ching-Min; Chen, Dar-Ren; Kuo, Shou-Jen (Frontiers in Oncology, 2021)
Objective: Endoscopic assisted breast surgery (EABS) or robotic assisted breast surgery (RABS) performed through minimal axillary and/or peri-areolar incisions has become the representative of minimal access breast surgery (MABS). We report the trend and clinical outcome of MABS for treatment of breast cancer. Methods: Information on patients who underwent breast cancer operations by principal investigator during the period of 2011 to 2020 were collected from single institute for analysis. The clinical outcome, trend and cost of MABS were analyzed and compared with conventional breast surgery (CBS). Results: A total of 824 breast cancer patients operated by single surgeon were enrolled in this study: 254 received CBS, and 570 received MABS, including 476 EABS and 94 RABS. From 2011 to 2020, the number of MABS performed annually has shown an increasing trend. Compared with CBS, MABS such as breast conserving surgery and nipple sparing mastectomy (NSM) have effectively reduce wound scar length. Since the sequential uprise from conventional NSM (C-NSM), dual-axillary-areolar-incision two dimensional (2D) endoscopic assisted NSM (E-NSM), single-axillary-incision E-NSM, robotic assisted NSM (R-NSM), and single port 3D E-NSM, the development of minimal access mastectomies increasingly paralleled with NSM. The operation time of various MABS decreased significantly and showed no statistical difference compared with CBS. R-NSM was associated with highest cost, followed by 3D E-NSM, E-NSM, and C-NSM. The positive surgical margin rate, and local recurrence rate of MABS and CBS were not statistically different.